2018
DOI: 10.1038/s41419-018-0484-2
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA TUG1 facilitates osteogenic differentiation of periodontal ligament stem cells via interacting with Lin28A

Abstract: Periodontal ligament stem cells (PDLSCs) are mesenchymal stem cells derived from dental tissues with multidirectional differentiation potential and excellent self-renewing ability. Recently, long noncoding RNAs (lncRNAs) have been shown to play important roles in MSC osteogenic differentiation. In this study, we found that taurine upregulated gene 1 (TUG1), an evolutionarily conserved and widely present lncRNA was significantly upregulated in osteogenically induced PDLSCs compared to their undifferentiated cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 61 publications
1
75
0
Order By: Relevance
“…Recently, lncRNAs have been reported to regulate bone formation and osteogenic differentiation of PDL stem cells. He et al [21] revealed that lncRNA TUG1 promoted osteogenic differentiation of PDL stem cells, and the mechanism might be related to Lin28A. Peng et al [22] suggested that lncRNA ANCR inhibited bone formation of PDL stem cells through miR-758/Notch2.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lncRNAs have been reported to regulate bone formation and osteogenic differentiation of PDL stem cells. He et al [21] revealed that lncRNA TUG1 promoted osteogenic differentiation of PDL stem cells, and the mechanism might be related to Lin28A. Peng et al [22] suggested that lncRNA ANCR inhibited bone formation of PDL stem cells through miR-758/Notch2.…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of the gene inhibited the osteogenic potential of periodontal ligament stem cells. Thus, TUG1 may regulate osteoblast differentiation by regulating the expression of Lin28 20 . Liao et al proposed that lncRNAH19 serves as the mediator of BMP9 signal transduction by regulating the Notch signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the pattern of TUG1 functioning encompassed from interacting with proteins to binding RNAs. He et al (32), reported TUG1 facilitated osteogenic differentiation of periodontal ligament stem cells via interacting with Lin28A. Zhang et al (33) presented TUG1 was required to target EZH2 occupancy and epigenetically modulate the expression of p15, p16, p21, p27 and p57, further regulated the cell proliferation.…”
Section: Discussionmentioning
confidence: 99%